AN ANALYSIS OF SPEECH ACTS USED BY THE SEVENTH-GRADE TEACHER OF SMPN 2 BANGLI IN EFL CLASSROOM INTERACTION - Ivana Swastiana, Ni Made; Putra I.N, Adi. J.; I.W, Suarnajaya (LPPM Undiksha, 2020)
Speech act is an action performed via utterances. This study investigated the types and functions of speech acts used by the seventh-grade English teacher at SMPN 2 Bangli by adopting Searle?s theory. The data were obtained through classroom observation and semi-structured interview. The data were analysed qualitatively by using Miles and Huberman?s interactive model. It was found out that there were five types of speech acts used by the teacher, namely representative, directive, expressive, commissive, and declaration in which directive (47.52%) was dominantly used by the teacher, while the declaration was the one which was less produced (0.71%). Among the functions of directive act, commanding appeared the most (44.40%), while naming and declaring were in the same amount in declaration type (50%). The teacher?s directive acts proved that she played her role to manage the classroom instructional system, to counsel the students and their learning, to instruct and to assess. However, the teacher, who also acted as the homeroom teacher and was in authority during the English lesson, performed the declaration act to change some situations in the classroom.